Is blue light solely detrimental for human eyes? A concise overview of the current knowledge on how blue light affects eye health. - Żurowska, Emilia; Guderska, Urszula; Krawiel, Karolina; Król, Marek; Kurzeja, Jacek; Markowska, Iga; Piotrowicz, Hubert; Piotrowicz, Katarzyna (Quality in Sport, 2024)
It has long been assumed that blue light is solely detrimental to the eyes and that it is a serious risk factor for a number of ocular diseases. In order to gain a more nuanced comprehension of the impact of blue light on the eye and to ascertain whether there are any beneficial aspects to this influence, this article presents a synthesis of the relevant research and offers updates on the current understanding of the subject matter. The review encompasses the environmental and societal changes that result in increased light exposure, the working principle and reasons for the prevalence of light-emitting diodes, and the safety classification of artificial light sources. Subsequently, we present the impact of blue light on ocular growth and the known mechanisms by which blue light affects different areas of the eye, including the cornea, conjunctiva, lens and retina. Finally, we discuss the validity of blue-blocking lenses and review other recommended strategies aimed at minimising the negative effects of blue light exposure.